Pengaruh Perkembangan Karier Dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan (Studi pada Karyawan Pasar Kranji Baru pada Kota Bekasi) - Haikal firdaus, Muhammad; Fayruz, Mohammad; Fauzi, Achmad; Meyrawati, Dyaz; Rahmanda Zulhidayani, Mega; Nathasyah, Nathasyah; Novita Ara, Sheren (Dinasti Review, 2023)
Every company does different things to achieve goals. Established before but not used to being apart from the main target to grow as well as developing the skills of our employees is that employees are company assets and one of its events. Employee professional development company is the motivational career growth of employees and employees. This writing uses the best quantitative method of learning. References To study the concept of the connection between variables which exist from the Google Scientist magazine with the online method as well as other mass media. There is an influence between career development and employee satisfaction. There is influence between work motivation on employee satisfaction. Work discipline training begins to apply to employee performance notification of employees to employees to make the maximum contribution to be able to achieve which goals are desired.